Macroeconomic channels of transmission of post-pandemic recovery strategies for African economies - Koffi Sodokin; Mawuli Couchoro; Kokou Wotodjo Tozo (Cogent Economics & Finance, 2022)
The Sar-Cov-2 pandemic that began in 2019 has significantly affected the global economy and, in particular, those of African countries. This paper analyzes possible intervention channels by African states to put their economies back on a sustainable growth path once the health crisis is under control. The paper proposes workable macroeconomic channels for these countries' recovery from post-pandemic periods by using historical data to conduct empirical analyses. The paper employs World Bank data and ILOSTAT for 54 African countries within the period 1990-2018. We use a post-Keynesian framework and the difference and system generalized method-of-moments to show that wages drive African economic dynamics in the short run. This is particularly true for Sub-Saharan African countries. In addition, foreign output, proxied by European Union output, has a positive and significant impact on Sub-Saharan African economies in the short and long run. The results highlight strategic policy measures for recovering African economies, including improving wages and deepening international economic relations, particularly with the Eurozone countries.
Keywords: E02; E23; E24; O55; 330; Covid-19; economic recovery; gross domestic product; profit; wage